Evaluation of the role of tax consultants in the tax audit process assistance services - Muhammad Arif Fahrizal; Siti Nuryanah (SEAN Institute, 2024)
The number of taxpayers audited has increased in 2022. The implementation of a higher frequency of tax audits has the potential to have a positive impact on state revenue. In order for a tax audit to achieve the expected results, tax inspectors must have access to relevant taxpayer information and obtain the cooperation of the taxpayers involved. Therefore, the demand against the taxpayer provides a reason for most taxpayers to choose to use the services of a Tax Consultant. The evaluation is carried out to analyze how the prices and benefits of tax consultants in their role in the tax audit assistance process services so as to provide satisfaction to clients. The evaluation is carried out based on the model of Price Dimension, and Cost-Benefit Theory. This research is qualitative research with a case study approach and is carried out by triangulation. In this study, the triangulation method was carried out by conducting surveys/questionnaires of taxpayers (tax consultant clients) and tax consultant interviews. The results of the evaluation of the role of tax consultants in assisting tax audit process services as measured by the Price Dimension and Cost-Benefit Theory show that tax audit assistance services as a whole provide satisfaction to clients. This is based on the ability of tax consultants to assist clients in accompanying their tax audits. The implication of this research is that tax audit assistance services can be carried out by considering price and the benefits so that in the future it can produce the tax audit results desired by clients.